Analyse multi-niveaux de l’activité en situation de formation : proposition méthodologique pour une étude synchronique et diachronique - Marlène Manach (Recherches en Éducation)
This paper proposes to give a report of the methodology of construction of empirical data based on a structuring of the social-technical approach (Albero, 2010a/b/c) and the theoretical framework of the course of action (Theureau, 2006, 2015), as part of an analysis of activity in training situation. This structuring aims to understand the activity of trainers and learners in a diachronic and synchronic perspective, interesting in the effect of social, material and symbolic dimension of training environment on activity and successive transformations.